Bank-specific and macro-economic determinants of profitability of Indian commercial banks: A panel data approach - Eissa A. Al-Homaidi; Mosab I. Tabash; Najib H. S. Farhan; Faozi A. Almaqtari (Cogent Economics & Finance, 2018)
This study aims at finding out the determinants of Indian commercial banks profitability. Profitability of Indian banks is measured by three important variables namely, Return on Assets (ROA), Return on Equity (ROE) and Net Interest Margin (NIM). The study also uses a set of independent variables such as bank-specific factors which include bank size, assets quality, capital adequacy, liquidity, operating efficiency, deposits, leverage, assets management and the number of branches. Pooled, fixed and random effects models and Generalized Method of Moments (GMM) are built on panel data of 10 years for more than 60 commercial banks of India. The study also takes into account Gross Domestic Product (GDP), inflation rate, interest rate and exchange rate as macroeconomic determinants. The results of the study show that all bank-specific factors, except the number of branches, exhibited significant impacts on profitability as measured by NIM. The findings also show that all macroeconomic determinants used in the study are found to be significant with negative impacts on Indian commercial banks profitability. Furthermore, the results show that bank size, number of branches, assets management ratio and leverage ratio are highly significant variables of profitability in the context of Indian commercial banks as measured by ROA. The results give a better insight into the Indian banking sector and the determinants of its profitability
Keywords: 330; bank-specific; macroeconomic; nim; profitability; panel data; GMM; India